Mammographies : The Cultural Discourses of Breast Cancer Narratives - DeShazer, Mary K. (Book collections on Project MUSE., 2013)
While breast cancer continues to affect the lives of millions, contemporary writers and artists have responded to the ravages of the disease in creative expression. This book looks specifically at breast cancer memoirs and photographic narratives, a category the author refers to as mammographies, signifying both the imaging technology by which most Western women discover they have this disease and the documentary imperatives that drive their written and visual accounts of it. The author argues that breast cancer narratives of the early twenty-first century differ from their predecessors in their bold address of previously neglected topics such as the link between cancer and environmental carcinogens, the ethics and efficacy of genetic testing and prophylactic mastectomy, and the shifting politics of prosthesis and reconstruction. This book is distinctive among studies of contemporary illness narratives in its exclusive focus on breast cancer, its analysis of both memoirs and photographic texts, its attention to hybrid and collaborative narratives, and its emphasis on ecological, genetic, transnational, queer, and anti-pink discourses. The author's methodology - best characterized as literary critical, feminist, and interdisciplinary - includes detailed interpretation of the narrative strategies, thematic contours, and visual imagery of a wide range of contemporary breast cancer memoirs and photographic anthologies. The author explores the ways in which the narratives constitute a distinctive testimonial and memorial tradition, a claim supported by close readings and theoretical analysis that demonstrates how these narratives question hegemonic cultural discourses, empower reader-viewers as empathic witnesses, and provide communal sites for mourning, resisting, and remembering. -- Publisher's description.